Simulation of the Extraction Efficiency of Coalbed Methane under Water Injection: A Gas-Liquid-Solid Coupling Model - Hai Pu; Liqiang Zhang; Xu Dong; Tao Jing; Xu Junce (Geofluids, 2020)
Coalbed methane is always a major hidden danger that affects mining safety in coal mines. In the study of coal seam water injection to control gas disaster, the increase of free water content is helpful to destroy the integrity of coal seam and to promote the flow of gas in fractures. However, when the free water fills the fracture space, it will increase the flow resistance of gas, and then will reduce the gas extraction efficiency. At present, there is currently no mathematical model describing the effects of coal seam water injection that combines these two aspects on gas drainage. In this study, a series of experiments were conducted to study the differences in mechanical property changes under wetting conditions with different coal samples. The experimental results show that the elastic modulus and compressive strength decrease as an exponential function with increasing water pressure. Based on the experimental results, a gas-liquid-solid coupling model including effective stress change and gas desorption is established and used to predict a field gas extraction application. According to the results of the numerical model, In the plastic failure zone of coal seam, the permeability increases, the elastic modulus drops and gas migrates faster. In the water wetting zone, the free water occupies the fracture space, which blocks the gas migration channel. The overall effect of water injection on gas extraction depends on which impact plays a dominant role. The established gas drainage model is validated by field data and can reflect the pattern of borehole damage and gas drainage under water injection.